Blow flies (Diptera: Calliphoridae) of the Baja California Peninsula - Stotelmyre, Lyle Magee (Zootaxa, 2024)
The blow fly fauna of the Baja California peninsula, Mexico has been sparsely documented. This study incorporates and lists recent and historical records of blow flies from collecting trips throughout the peninsula, visits to major southern California museums for historical collection records, and a literature search. Seven genera and 16 species are reported from the two peninsular Mexican States, Baja California, and Baja California Sur. Three species are recorded that are not included in the 2020 Catalog of Mexican Calliphoridae by Jaume-Schinkel, & Ibanez-Bernal (2020), they are: Calliphora livida, Calliphora terraenovae, and Calliphora vomitoria. One blow fly species, Cochliomyia hominivorax (the primary Screw-Worm Fly) is not included here but is found in museum collections. Once present in Baja, it is considered eradicated from continental North America as far south as the Panama Canal by the U.S. Department of Agriculture (USDA) however, it is occasionally reintroduced (Skoda et al. 2018) and is still present in some Caribbean islands. It is noteworthy that all calliphorid species from this mountainous desert peninsula are also found in the State of California, USA which supports 11 genera and 47 species in this family (Whitworth 2006) primarily because of its more varied climate and terrain. The Baja peninsula can be considered a southern extension of the State of California, with reduced species representation due to reduced climate and terrain variation, so no separate identification keys are necessary. Forensic entomologists and taxonomists can use the blow fly keys for North America by Whitworth, 2006, and 2017 for this region. The latest key by Jones, Whitworth, and Marshall (2019) is revolutionary and much welcome in taxonomy in that it is an online computer-aided key that has actual macro-photos of species identification characters and is intended to be used with a computer screen next to your microscope for identifications in place of printed material.